REPRESENTATION TRANSLATION ANALYSIS OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING MATHEMATICS PROBLEMS - Swastika, Galuh Tyasing; Nusantara, Toto; Subanji, Subanji; Irawati, Santi; As?ari, Abdur Rahman; Irawan, Edy Bambang (Universitas Negeri Malang, 2018)
This research aims at analyzing the representation translation of Junior High School students in solving mathematical questions related to algebra. This research used descriptive qualitative approach. The focus of representation translation used in this research was the external representation which was a verbal translation into diagram, verbal into symbolic, symbolic into diagram, diagram into symbolic, and diagram into verbal. Based on the analysis of research findings, it shows that representation translation of students from verbal, symbolic, and diagram into verbal and diagram was not really mastered by the students. Meanwhile, the representation translation into symbolic was frequently used by the students although they were expected to do other translation rather than symbolic.